ENTREPRENEURSHIP BAGI UMMAT ISLAM - Retnanto, Agus (EQUILIBRIUM, 2014)
Learning social sciences, including about economics should be necessary to study the most fundamental ideas that gave birth to the science and economic system. If we examine more deeply about economic policy built on the idea of capitalist economic system, then we can know the depravity of the system and contradiction with Islam. We can see clearly the thoughts of Islamic economics. Islamic economic thought that this could provide a solution to the problems existing economic life with appropriate solutions and make a distinctive life style, as opposed to capitalist life, both related to the subjects and aspects details.According to Islamic law, the vision, mission, and goals of the business management should explain the orientation of Islamic law. His vision is to make the business as a vehicle for business managers to achieve profits shaded pleasure of God. Mission and goals that integration is not to realize the existence of the Human Resources professional who has the maturity of personality (syakhsiyyah) Islam, through the mindset and attitude of Islamic patterns. Maturity will be reflected in the business orientation and activity of every Muslim Human Resources. On the basis of the law anyway, strategic step for every Muslim activities of the Human Resources is the law itself. It is as a rule of usul, which states, "Al-aslu fil-af al at-taqayyadu bil-hukmisy-Shar'ie" legal origin bound action on five rules of Islam (ie mandatory, sunnah, permissible, makruh, or unlawful) .There are 3 formulation of the problem that can offer a solution to the Efforts in the economic prosperity of the people, (1) How can Muslims unresolved issues of sufficiency economy, (2) How do we attempt to move mentally Muslims in entrepreneurship so as to rise from the hegemony of economic system of capitalism, (3) tips and solutions what can we build to foster an entrepreneurial spirit for Muslims to Become prosperous life.Keywords: entrepreneurship for MuslimsBelajar ilmu sosial, termasuk tentang ekonomi harus diperlukan untuk mempelajari ide-ide yang paling mendasar yang melahirkan ilmu dan sistem ekonomi. Jika kita mengkaji lebih dalam mengenai kebijakan ekonomi yang dibangun di atas gagasan sistem ekonomi kapitalis, maka kita dapat mengetahui kebobrokan sistem dan bertentangan dengan Islam. Kita bisa melihat dengan jelas pikiran ekonomi Islam. Pemikiran ekonomi Islam bahwa hal ini dapat memberikan solusi terhadap permasalahan yang ada kehidupan ekonomi dengan solusi yang tepat dan membuat gaya hidup yang khas, sebagai lawan kehidupan kapitalis, baik terkait dengan mata pelajaran dan rincian aspek. Menurut hukum Islam, visi, misi, dan tujuan dari manajemen bisnis harus menjelaskan orientasi hukum Islam. Visinya adalah untuk membuat bisnis sebagai kendaraan untuk manajer bisnis untuk mencapai keuntungan berbayang kesenangan Allah. Misi dan tujuan integrasi yang tidak menyadari keberadaan SDM profesional yang memiliki kematangan kepribadian (syakhsiyyah) Islam, melalui pola pikir dan sikap pola Islam. Kematangan akan tercermin dalam orientasi bisnis dan aktivitas setiap Muslim Sumber Daya Manusia. Atas dasar hukum pula, langkah strategis untuk setiap kegiatan Muslim Sumber Daya Manusia adalah hukum itu sendiri. Hal ini sebagai aturan ushul, yang menyatakan, "Al-aslu fil-af al at-taqayyadu bil-hukmisy-syar'i" hukum asal terikat tindakan pada lima aturan Islam (yaitu wajib, sunnah, mubah, makruh, atau melanggar hukum).Ada 3 rumusan masalah yang dapat menawarkan solusi untuk Upaya kesejahteraan ekonomi masyarakat, (1) Bagaimana Muslim masalah yang belum terselesaikan ekonomi kecukupan, (2) Bagaimana kita mencoba untuk bergerak mental umat Islam dalam kewirausahaan sehingga bangkit dari hegemoni sistem ekonomi kapitalisme, (3) tips dan solusi apa yang bisa kita membangun untuk menumbuhkan semangat kewirausahaan bagi umat Islam untuk menjadi kehidupan yang sejahtera.Kata kunci: kewirausahaan bagi umat Islam